El niño y lo melodramático. Tres hipótesis aplicadas al cine argentino de la postdictadura - Sophie Dufays (Caravelle)
Based upon a brief reminder of the role and melodramatic potential of childrens’ characters in Latin American cinema, this article analyzes how this same potential has been developped in some ten Argentinian films after the end of the dictatorship, which evoke a historical context and whose plot revolves around the father’s absence (death, disappearance).